BRCA1 and BRCA2 Gene Mutations and Colorectal Cancer Risk: Systematic Review and Meta-analysis. (31st October 2018) - Oh, Mok; McBride, Ali; Yun, Seongseok; Bhattacharjee, Sandipan; Slack, Marion; Martin, Jennifer R; Jeter, Joanne; Abraham, Ivo
Abstract: Background: Investigations of the associations with colorectal cancer have yielded conflicting results. The aim of our study was to synthesize the research on colorectal cancer risks in BRCA mutation carriers by means of a systematic review and quantitatively by means of meta-analyses overall and in subgroups of BRCA mutation carriers. Methods: We searched PubMed/MEDLINE, Embase, Cochrane, Scopus, and ProQuest Dissertation & Theses. Unadjusted odds ratios (ORs) were used to derive pooled estimates of colorectal cancer risk overall and in subgroups defined by mutation type ( BRCA1 or BRCA2 ), cancer type (colorectal or colon cancer), study design (age–sex-adjusted or crude), and ascertainment method (ascertained or inferred genotyping). The associations were evaluated using random-effect models. All statistical tests were two-sided. Results: Eighteen studies were included in the systematic review: five cohort studies with ascertained BRCA mutation, six cohort studies involving pedigree analysis, five case–control studies, and two kin–cohort studies. Of these, 14 were used in the meta-analysis, which revealed a statistically significant increased risk of colorectal cancer in overall BRCA mutation carriers (OR = 1.24, 95% confidence interval (CI) = 1.02 to 1.51, P = .03). In subgroup meta-analyses by BRCA type, BRCA1 mutation was associated with increased risk of colorectal cancer (OR = 1.49, 95% CI = 1.19 to 1.85, P < .001), but BRCA2 was not (OR = 1.10, 95% CI = 0.77 to 1.58, P = .61). In subgroup meta-analyses of studies reporting estimates adjusted for age and sex, an increased risk of colorectal cancer for BRCA1 (OR = 1.56, 95% CI = 1.23 to 1.98, P < .001), but not for BRCA2 (OR = 1.09, 95% CI = 0.75 to 1.58, P = .66) was observed. Analyses stratified by ascertainment method found no association between BRCA mutation and colorectal cancer risk. Conclusion: The meta-analysis results provide clinicians and health-care regulatory agencies with evidence of the increased risk of colorectal cancer in BRCA1 mutation carriers, but not in BRCA2.